When Group Influence Is More or Less Likely: The Case of Moral Judgments. Issue 6 (2nd November 2019) - Cornwell, James F. M.; Jago, Carl P.; Higgins, E. Tory
Abstract: We investigated whether group influence can change judgments even for high-consensus (i.e., unambiguous) moral norms. We found that participants often matched the judgment of the other current group members even when this moral judgment was normatively incorrect (nonstandard), and this occurred more for more ambiguous issues. Moreover, this social influence on public judgments was generally followed by private agreement and re-interpreting general values to be consistent with those judgements. We also found that participants who experienced a fit between their regulatory focus and their feelings of power (i.e., promotion/high power; prevention/low power) were less influenced by the group.